An exploratory study based on shopping centers in Hong Kong examined the relationship between impact marketing strategies, promotional components, and customer retention. - ZHANG XIANGHAN; ABHIJIT GHOSH (International Journal of Multidisciplinary Research and Studies, 2023)
The relationship between the marketing strategy and the customer retention of the shopping centre industry in Hong Kong, as well as the identification of the major components of the marketing strategy that are used to enhance and maintain customer loyalty to the shopping centres. Over the course of the last several decades, there was a significant expansion of the economic development. Customers' shopping habits have also changed significantly, shifting from purchasing goods in general stores to enclosed shopping malls that feature a relaxing atmosphere and air-conditioning facilities. This shift has contributed to the development of favourable conditions and an ambiance favourable to the rapid expansion of the shopping centre industry. As a result of the intense competition that exists between shopping centres and the growing recognition of the significance of maintaining customer loyalty within the shopping centre industry, the manager of a shopping centre has placed a greater emphasis on analysing how the shopping center's marketing strategy can assist in maintaining the shopping center's existing clientele in order to boost the shopping center's patronage and rental income. It has been determined via an analysis of the relevant literature what the most important aspects of the marketing strategy for the shopping centre business are. The purpose of the customer survey conducted at big scale shopping centres across a variety of countries was to further examine the customers' thoughts on a variety of marketing components that would effect their decision making to return to the shopping mall. The survey demonstrates that there is a connection between customer satisfaction and customer retention. It found that customers who visited the shopping centre more frequently during the course of a week reported being more satisfied with the services provided by the shopping centre. This finding suggests that customers' feelings of contentment may play a role in the shopping center's ability to keep them as patrons. The findings of the poll indicate that returning customers are more inclined to spend more money on their shopping, which suggests that if shopping centres can successfully keep their current consumers, they will be able to increase their overall performance and return on investment.